Biochemical, Microbiological, and Physiological Markers of NAFLD in Obesity: The Role of GGT, Ferritin, and Gut Microbial Dysbiosis, Including LPS-Producing Bacteria and SCFA Alterations - Bilal Ilyas, Mahwish Shahzad, Sardar Ahmad, Mariam Danish Iqbal, Aisha Liaqat, Sonia Tahir (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Evaluation of gamma-glutamyl transferase (GGT), serum ferritin, and specific gut microbiomealterations—including lipopolysaccharide (LPS)-producing bacteria and short-chain fatty acid(SCFA) profiles—was conducted in obese individuals to identify biomarkers predictive of nonalcoholic fatty liver disease (NAFLD).